2022
DOI: 10.1186/s12889-022-13981-5
|View full text |Cite
|
Sign up to set email alerts
|

Improving access to public physical activity events for disadvantaged communities in Australia

Abstract: Background Physical activity has numerous health benefits, but participation is lower in disadvantaged communities. ‘parkrun’ overcomes one of the main barriers for disadvantaged communities, the cost of activities, by providing a free, regular community-based physical activity event for walkers, runners and volunteers. This study assesses equity of access (in terms of distance to the nearest parkrun) stratified by socioeconomic deprivation, and identifies the optimal location for 100 new event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…Significantly for PA interventions more broadly is the association between lower SES and the high-growth participation pattern. Although parkruns are more likely to be in more advantaged areas, 32 one-third of our sample were in the lowest 3 deciles. Research from the United Kingdom on approximately 60,000 parkrunners has shown that those from areas of greater disadvantage who are inactive at registration report greater improvements in fitness, physical health, happiness, and mental health when compared to the whole sample.…”
Section: Discussionmentioning
confidence: 69%
“…Significantly for PA interventions more broadly is the association between lower SES and the high-growth participation pattern. Although parkruns are more likely to be in more advantaged areas, 32 one-third of our sample were in the lowest 3 deciles. Research from the United Kingdom on approximately 60,000 parkrunners has shown that those from areas of greater disadvantage who are inactive at registration report greater improvements in fitness, physical health, happiness, and mental health when compared to the whole sample.…”
Section: Discussionmentioning
confidence: 69%
“…As route design could influence whether first-timers return, parkrun might want to consider the mechanism by which new events are created and whether they can add more flexibility to these processes to encourage the introduction of more parkruns with characteristics associated with higher return rates. For example, parkrun have prioritised the creation of events on socio-economic grounds after inequalities were identified in the distribution of parkrun events in England [ 51 ]. After receiving funding to create 200 new events a study identified the ideal locations to reduce these inequalities [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Se ha estimado incluso que la inactividad física aumenta el gasto en salud en todos los países entre un 1.2 y 2.5%, por lo que promover el ejercicio físico acrecienta el costo-beneficio y el costo-utilidad global en las naciones y se traduce en un enorme provecho para las personas 41,42 . Se ha establecido que la selección estratégica de lugares donde se puede realizar actividad física cerca de comunidades desfavorecidas con desventajas para su acceso, a comparación de otras más favorecidas, mejora en esas comunidades la equidad y la participación de la población, teniendo un impacto benéfico en la salud pública 43 .…”
Section: ¿El Ejercicio Físico Es Económico?unclassified